Non-verbal cues: an inevitable assesing skils in doctor-patient relationship - AL Khalib,; AB Madihah, (Department Of Community Health, Faculty of Medicine, Universiti Kebangsaan Malaysia, 2010)
Introduction: Non-verbal cues are untold words that carry a significant meaning. As a doctor, this remark needs to be perceived correctly. It is an inevitable communication knowledge and skills ought to be mastered in any doctorpatient relationship, particularly when making patient’s assessment. Methodology: This was a systematic communication assessment of a real observations on doctor-patient relationship in various setting. It was supported by feedbacks from many scholars who were involved in research and teaching and also reviews, papers and studies on the said subject. Results: It has been realized that non-verbal communication was equally important and necessary to complement the verbal one. From all non-verbal cues we have recognized and listed, we have identified at least ten to be the most vital areas to be observed while counseling or consulting a patient. Conclusion: Non-verbal cues were always present to support doctor in making a final conclusion about his/her patient’s state. If doctor was patience enough, he or she could has a complete profile of his/her patient and this would lead to the improvement in a person’s life. Having an observant attitude and being able to nose around appropriately were skills that have to be learnt, experienced and applied as these might make an effective doctor-patient communication.